EVALUASI PENERAPAN PENGELOLAAN KEUANGAN DESA NGGESA BIRI BERDASARKAN PERMENDAGRI NOMOR 20 TAHUN 2018 (Studi Pada Desa Nggesa Biri Kecamatan Detukeli Kabupaten Ende) - Ida, Maria Fariyanti; Reo, Hermanus; Sayang, Sabulon (Program Studi Akuntansi Universitas Flores, 2022)
This study aims to find out how financial management in Nggesa Biri Village is in accordance with Minister of Home Affairs Regulation No. 20 of 2018 concerning village financial management. the data used are primary and secondary data, then analyzing the data using interview and documentation methods. The population chosen is the financial reports of the village of Nggesa Biri, Detukeli District, with a sample of the financial reports for the village of Nggesa Biri, Detukeli District, for 2020-2021. The results of the study show that financial management in Nggesa Biri Village in the planning, implementation, administration, reporting and accountability stages in 2020-2021 basically applies Minister of Home Affairs Regulation No. 20 of 2018 in managing village finances, there are only a few things that need to be addressed. note that in the administration stage it needs to be improved again, at the reporting stage it is still late in submitting reports on the realization of the APBDesa implementation and the Accountability Stage there are also delays in submitting accountability reports and reports on the realization of APBDesa implementation and accountability reports are not transparently submitted to the public.